Pengaruh Kompetensi, Beban Kerja dan Fasilitas Kerja terhadap Kinerja Guru SMA Sekecamatan Dukupuntang dengan Motivasi Kerja sebagai Moderasi - Alpij Albar Rosayu; Didik Harjadi; Dede Djuniardi (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2023)
Research objectives: 1) analyze the effect of competence on teacher performance 2) analyze the effect of workload on teacher performance 3) analyze the effect of work facilities on teacher performance 4) analyze work motivation in moderating the effect of competence on teacher performance 5) analyze work motivation in moderating the influence of load work on teacher performance 6) analyze work motivation in moderating the effect of work facilities on teacher performance. The population in this study were all teachers in high schools in the Dukuntang district, namely Dukuntang 1st High School, Unggulan Bina Insan Mulia High School, Kramat Dukuntang High School and Yapisa Dukuntang High School. The total population is 100 teachers. The sampling technique uses a saturated sample.The number of samples is also 100 teachers.The analytical method used is the SEM analysis method with the SmartPLS analysis tool. The results of the study: 1) competence has a positive and significant effect on teacher performance. 2) workload has a positive and significant effect on teacher performance. 3) work facilities have a positive and significant effect on teacher performance. 4) work motivation cannot moderate the influence of competence on teacher performance. 5) work motivation cannot moderate the effect of workload on teacher performance. 6) work motivation cannot moderate the effect of work facilities on teacher performance.